(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Although prolonged survival following hanging is common, it is rare after strangulation. Early rescue may take place in hanging, rather than strangulation. In addition, the amount of constricting force applied to the neck is less in hanging than strangulation. We are reporting a case of strangulation where the victim survived for more than 5 days.